Estratégias de ensino da leitura: caminhos para a compreensão global do texto - Bernardi, Marilisa Cardoso (2008)
This dissertation follows the line of research in Portuguese Teaching, Reading, and Writing, and aims at contributing to studies in development of reading competencies of students at Fundamental Education. In Brazil, official rates of students performance in reading competencies show that reading ability is far below the ideal, and that actions to improve teaching quality are required. According to the most recent reports from Sistema Nacional de Avaliação da Educação Básica (Saeb) [National System of Fundamental Education Evaluation], as few as ten percent of the students evaluated achieved adequate level of reading. This research was conducted to verify, specifically, the performance of students at 8th grade of Fundamental Education in reading competency of theme identification, and to identify strategies for teaching reading that help to seek a global text comprehension. The corpus analysed consists of reading activities included in two textbooks used in the public education system. The results show that reading activities in one of the books analysed were consistent with theorical principles studied, and, thus, were considered activities that allow identify the text theme. The activities analysed in the other textbook don t present a good interpretive clue due to the inadequacy of the comprehension questions for the subjectivity in the language and the complexity of the texts selected. Regarding text methodological approach, we hope this paper contribute to improve text global comprehension